Coronavirus COVID- 19: A critical review of its history, pathogenesis, transmission, diagnosis and treatment (2020)
The outbreak of the deadly virus (novel coronavirus or Severe Acute Respiratory Syndrome Coronavirus-2) that emerged in December 2019, remained a controversial subject of intense speculations regarding its origin, became a worldwide health problem resulting in serious coronavirus disease of 2019 (acronym COVID-19). The concern regarding this new viral strain ―Severe Acute Respiratory Syndrome Coronavirus-2‖ (acronym SARS-CoV-2) and diseases it causes (COVID-19) is well deserved at all levels. The incidence of COVID-19 infection and infectious patients are increasing at a high rate. Coronaviruses (CoVs), enclosed positive-sense RNA viruses, are distinguished by club-like spikes extending from their surface, an exceptionally large genome of RNA, and a special mechanism for replication. Coronaviruses are associated with a broad variety of human and other animal diseases spanning from enteritis in cattle and pigs and upper chicken respiratory disease to extremely lethal human respiratory infections. With world health organization (WHO) declaring COVID-19 as pandemic, we deemed it necessary to provide a detailed review of coronaviruses discussing their 2019 Novel Coronavirus, history, current situation, coronavirus classification, pathogenesis, structure, mode of action, diagnosis and treatment, the effect of environmental factors, risk reduction and guidelines to understand the virus and develop ways to control it.